PROVEAN web server: a tool to predict the functional effect of amino acid substitutions and indels - Choi, Yongwook; Chan, Agnes P. (Bioinformatics, 2015)
We present a web server to predict the functional effect of single or multiple amino acid substitutions, insertions and deletions using the prediction tool PROVEAN. The server provides rapid analysis of protein variants from any organisms, and also supports high-throughput analysis for human and mouse variants at both the genomic and protein levels. Availability and implementation: The web server is freely available and open to all users with no login requirements at http://provean.jcvi.org. Contact:  achan@jcvi.org Supplementary information:  Supplementary data are available at Bioinformatics online.